Cow's Milk Protein Sensitive Enteropathy. Clinical and Histological Features in Infants - A. H. Sutanto (Paediatrica Indonesiana, 1982)
The terms "cow's milk allergy", "cow's milk protein intolerance", "cow's milk protein sensitive enteropathy", and "latent cow's milk intolerance" were discussed.Cow's milk protein intolewnce zs thollljht to be due to sensitisation caused by macronwlecufar tlbsotption.Diarrhea with dehydration, electrolyte imbalance, malabsorption and failure to thrive in early infancy are the primary symptoms.Histological changes can be found in the stomach and small intestine. The small intestinal mucosa exhibits a patchy mtt!ropathy with villus atrvphy, cellular infiltration wzd increased intraepitheliial lymphocytes.It has been shown that the assay of immunoglobulin and complement levelsin the serum and duodenal juice is not useful in the diagnosis of CMPSE.